REDEFINING MEDICINE: A CRITICAL REVIEW OF EMERGING INNOVATIONS SHAPING THE FUTURE OF HEALTHCARE - Saleh salem saleh Alkhamsan, Salem Nasser Mohammed Al khamsan, Alhassan Ali Salem Al Zulayq, Saleh Ali Salem Al-Zulaiq, Fatima Essa Saad Alqahtani, Hussien Ali Mohammed Almuhamidh, Fawzeaha Saadi Hassan Almotiri (Chelonian Research Foundation, 2023)
The healthcare sector stands on the cusp of a transformative era, fueled by a confluence of technological, biomedical, and public health innovations. This critical review explores the multifaceted advancements poised to redefine medical practices, enhance patient care, and streamline healthcare delivery systems. From the integration of artificial intelligence (AI) and telemedicine to breakthroughs in gene editing and regenerative medicine, these innovations offer promising prospects for personalized and efficient healthcare solutions. However, they also introduce complex ethical, regulatory, and accessibility challenges that warrant careful consideration. By examining the potential impacts and limitations of these emerging technologies, this article aims to provide a comprehensive understanding of the innovations shaping the future of healthcare. It highlights the need for a balanced approach that fosters innovation while addressing the ethical dilemmas and disparities that accompany technological advancement. The future of healthcare, as depicted in this review, is one of immense potential tempered by the imperative to navigate the accompanying challenges judiciously. Keywords: Healthcare Innovation, Artificial Intelligence in Medicine, Telemedicine, Personalized Medicine, Gene Editing, Regenerative Medicine, Healthcare Ethics, Medical Technology Regulation, Digital Health, Healthcare Accessibility